(untitled) (Scientific journal of the Fergana State University, 2023)
On the basis of official documents and factual material the history of creating a system of non-state and non-profit organizations for the disabled in achieving their economic and social welfare is illustrated, furthermore, the creation of a social protection mechanism for persons with disabilities, developed in the years of independence of Uzbekistan is revealed.